Early diagnosis and successful treatment of acquired toxoplasmosis infectious retinochoroiditis: A case report. Issue 26 (June 2018) - Lv, Xiaoli; Yu, Pingping
Abstract: Rationale: Toxoplasma gondii is distributed worldwide, infecting a large population. It can cause focal necrotic retinitis or retinochoroiditis in the human eyes and is one of the most common causes of posterior uveitis. Patient concerns: A 68-year-old patient with normal immunity was complained about blurred vision and black shadow in the right eye for 1 week. Diagnoses: Combined Yellow-and-white bulged lesions in the fundus of the right eye with the Goldmann-Witmer coefficient = 2 and based on the serological indicators, we considered the diagnosis of T. gondii infection-induced retinochondritis. Interventions: Acetylspiramycin 0.4 QID × 3 weeks, concussive 20 days treatment after 3 days, for a total of 3 months, prednisone 20 mg/day with a weekly reduction of 5 mg for 1 month. Outcomes: After oral acetylspiramycin, topical and systemic corticosteroids for 3 months, the retinal lesions were scarred, and inflammation of the anterior chamber and vitreum disappeared. After a 9-month follow-up, the visual acuity was 0.6, and no active lesions were observed in the fundus. Lessons: The immunocompetent elderly who are in contact with domestic cats may have an opportunistic infection with toxoplasmosis leading to primary retinochoroiditis. Prompt diagnosis and effective treatment can get a good clinical prognosis.